Non-Syndromic Solitary Neurofibroma in floor of the mouth: A case report (Indian Journal of Case Reports, 2019)
Neurofibromas are rare in the head and neck region, but most frequent tumor of neural origin. Oral hard and soft tissue is affected by the tumor. In this paper, we describe an unusual case of non-syndromic solitary neurofibroma of the floor of the mouth in a 70-yearfemale patient with a chief complaint of growth in the floor of the mouth for the past 3 months. An occlusal, intraoral periapical radiograph and CT imaging were done. After confirming the diagnosis, the lesion was excised under local anesthesia and the specimen was submitted for histopathological examination. On subsequent follow-up, the patient was asymptomatic. Intraoral neurofibroma although uncommon, deserve special attention because of their similarity with other inflammatory neoplastic condition, and their tendency to undergo malignant transformation.